2020
DOI: 10.1111/1365-2745.13523
|View full text |Cite
|
Sign up to set email alerts
|

Variations in tree growth provide limited evidence of species mixture effects in Interior West USA mixed‐conifer forests

Abstract: In mixed stands, species complementarity (e.g. facilitation and competition reduction) may enhance forest tree productivity. Although positive mixture effects have been identified in forests world‐wide, the majority of studies have focused on two‐species interactions in managed systems with high functional diversity. We extended this line of research to examine mixture effects on tree productivity across landscape‐scale compositional and environmental gradients in the low functional diversity, fire‐suppressed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
(117 reference statements)
0
0
1
Order By: Relevance
“…The lack of evidence for a P. tremuloides mixture effect on P. menziesii growth contrasted with the results of a previous study that found P. menziesii growth increased with relative density of phylogenetically similar conifers in Interior West stands impacted by fire exclusion (Looney et al, 2020). The low shade tolerance of P. tremuloides, coupled with high potential height growth in P. F I G U R E 4 Predicted tree recruitment presence-absence for Populus tremuloides (POTR), Pseudotsuga menziesii (PSME), Pinus contorta (PICO) and Abies lasiocarpa (ABLA).…”
Section: Effects Of Species Mixture and Climate On Growthcontrasting
confidence: 99%
“…The lack of evidence for a P. tremuloides mixture effect on P. menziesii growth contrasted with the results of a previous study that found P. menziesii growth increased with relative density of phylogenetically similar conifers in Interior West stands impacted by fire exclusion (Looney et al, 2020). The low shade tolerance of P. tremuloides, coupled with high potential height growth in P. F I G U R E 4 Predicted tree recruitment presence-absence for Populus tremuloides (POTR), Pseudotsuga menziesii (PSME), Pinus contorta (PICO) and Abies lasiocarpa (ABLA).…”
Section: Effects Of Species Mixture and Climate On Growthcontrasting
confidence: 99%